Distribuição e roteirização de cargas: um estudo de caso em uma transportadora de Araguaína - TO. - Silva, Jaires Dias (Universidade Federal do Tocantins, 2020)
The distribution and routing contribute to achieve organization, planning and the best performance in every operation in the transportation management allowing the optimal solution for a specific problem of routes to meet the delivery points. This article aims to present the distribution and routing of loads employed in a carrier, with the focus on their fundamental factors and their respective processes that help solve problems of roadmaps to meet the road transport service. Through the bibliographic research and case study carried out in a specialized transportation company in the city of Araguaína - TO. In this way, the company offers solutions to vehicle routing problems seeking the highest possible yield, with strategies that help to achieve cost reduction and better time use to meet the demands of their respective customers.